Hubungan Kualitas Asupan dengan Kadar Glukosa Darah dan Working Memory pada Remaja SMP Kota Malang: The Relationship of Intake Quality with Blood Glucose Level and Working Memory in Middle-School Adolescents in Malang City - Muharrama, Tsania Nur; Kustiyah, Lilik; Dwiriani, Cesilia Meti (Departemen Gizi Masyarakat, Fakultas Ekologi Manusia, IPB dan PERGIZI PANGAN Indonesia, 2025)
Adolescents are an age group that tends to skip breakfast. A breakfast is a morning meal before starting the day's activities. The role of breakfast is very important for the performance and academic achievement of adolescents, especially to increase the academic performances and achievements in adolescents notably for those who are active in academic or school activities. The series of processes of the role of intake and academic achievement are closely related with the quality of intake and one of the cognitive functions, namely, working memory ability. The purpose of this study was to determine the relationship between intake quality, blood glucose levels, and working memory in adolescents attending junior high schools in Malang City. This study used a cross-sectional research model with a sample size of 42 subjects. Subjects were aged between 12-15 years from SMP Negeri 25 Malang City. Data consisted of subject characteristics (age, sex, pocket money), family characteristics (parents' monthly income, last education and occupation, number of family members), quality of intake using the DQI-A component, blood glucose levels, and working memory ability using the Working Memory Questionnaire (WMQ) score. Analysis used SPSS 16.0 to determine the distribution of data and test the relationship through bivariate analysis between the quality of intake, blood glucose levels and working memory in the subjects. There was no relationship between the quality of intake and DQI-A components, blood glucose levels, and working memory (p>0.05).